Supporting the National Framework for Climate Services in Guatemala and the Nationally Appropriate Mitigation Action on Sustainable Livestock in El Salvador - Hernandez Quevedo, Monica Paola; Martinez, Karen Michelle; Ruden, Alejandro; Costa, Ciniro; Navarro Racines, Carlos Eduardo (CGIAR System Organization, 2025)
The Livestock and Climate Initiative helped governments find ways to reduce the impacts of climate variability on livestock producers. Under Work Package 5, our implementing partner, the Alliance of Bioversity International and CIAT (the Alliance), worked with the government and other stakeholders in Guatemala to establish a regulatory framework aimed at creating a governance and coordination instrument to strengthen the country’s climate information services, and ultimately help reduce annual livestock losses from floods and droughts. The National Framework for Climate Services (NFCS) will be a major government policy instrument able to influence the creation or modification of government policies and regulations for future climate services. In El Salvador, the policy work of the Alliance focused on helping develop a Nationally Appropriate Mitigation Action (NAMA) for sustainable livestock.